PENGARUH PELATIHAN PEGAWAI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI DINAS KOPERASI DAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) KABUPATEN KUBU RAYA - Riyan Trihadi E.42008010 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
Writing this thesis aims to analyze the factors that affect employee productivity in the Dinas Koperasi danUsaha Mikro, Kecil, dan Menengah (UMKM) Kubu Raya district, especially on employee training factors. The titleof this thesis selected researchers to determine whether the employee training really affect employee productivity ingovernment agencies, so as to provide input to the government in improving employee productivity particularly inthe Dinas Koperasi dan Usaha Mikro, Kecil, dan Menengah (UMKM) District Kubu Raya. Location of research inthe Dinas Koperasi dan Usaha Mikro, Kecil, dan Menengah (UMKM) Kubu Raya district. The research sampleemployee 24 people who attended pelatiahan pelatiahan technical and structural. The conclusion of this research isemployee training have an influence on the productivity of employees working in the Dinas Koperasi dan UsahaMikro, Kecil, dan Menengah (UMKM). The influence of employee training on employee productivity by 46.4 and53.6% of the remaining influenced by other variables not included in this study such as physical and mentalcondition of employees, the relationship between superiors and subordinates, or other variables that can bedeveloped for further research. Key Word : employee training , employee productivity